Comparison Study of Analysis of Water Tower Structure Using Finite Element Method and Engineering Equation Solver - Nanang Qosim; Putra M Pamungkas; Barkah Fitriyana; Wanda Pratomo; Marthan Lassandy (Jurnal Teknologi Terapan, 2018)
This study aims to compare the analysis results of the maximum deformation and maximum stress on water structure using finite element method and engineering equation solver (EES). Simulation results show that verification successfully performed, with deformation value obtained is convergent to certain value with maximum percentage of 0,40%. Further, the maksimum stress value is still under the allowable stress of material 160 MPa. Hence, the structure of water tower with a capacity of 500 liters is safe to use. The result of calculation using EES shows that the deformation value is 1.70 mm. This value is different about 0.31 or 18.24% compared to the deformation value of 2.01 mm using fine meshing on ANSYS.